Human subcutaneous dirofilariasis caused by Dirofilaria immitis in a Greek adult - Evangelos Falidas; Stavros Gourgiotis; Olga Ivopoulou; Ioannis Koutsogiannis; Christianna Oikonomou; Konstantinos Vlachos; Constantinos Villias (Elsevier, 2016)
Summary: Human dirofilariasis is a zoonotic infection caused by worms of the genus Dirofilaria. Most reported cases involve Dirofilaria repens, and D. immitis infection has been rarely reported. Canines act as a reservoir for the infection, while human infections are sporadic. Human dirofilariasis has been widely reported in South Europe; however, the worldwide distribution constantly changes. We herein report an extremely rare case of subcutaneous trunk dirofilariasis in a 45-year-old immunosuppressed woman, caused by D. immitis. The parasitic infection was detected using ultrasonography. The infection was confirmed by a polymerase chain reaction-based method and was attributed to D. immitis. Keywords: Human, Dirofilariasis, Zoonotic infection, Worm, Dirofilaria immitis